PERBANDINGAN FREKUENSI LATIHAN SENAM AEROBIK LOW IMPACT TERHADAP INDEKS MASSA TUBUH (IMT) DAN TINGKAT RESIKO CEDERA OLAHRAGA MEMBER PEMULA WANITA SENAM AEROBIK KELOMPOK USIA 25 40 TAHUN DI SURABAYA BARAT - Kunjung Ashadi Abdul Hafidz, (Arena, 2010)
ABSTRACT This reseach done as a mean to detect low impact aerobic exercise frequency difference toward body mass index change and level of sport injury risk in 25-40 year old women beginner member group in west Surabaya teritory. In this reseach used pretest and postest quasy experiment design by using three treatment group within during eight weeks. Based on data analysis test result uses pair T test and one way anova known that low impact aerobic exercise frequency difference influential  towards body mass index change and level of sport injury risk.Higher exercise frequency/week in parallel with heavy body depreciation average, where is  exercise 5X / week has highest sport injury risk. Key words       : low impact aerobic, member, exercise frequency, sport injury